Cost-effectiveness and budget impact of heat-stable carbetocin compared to oxytocin and misoprostol for the prevention of postpartum hemorrhage (PPH) in women giving birth in India - John R. Cook; Kunal Saxena; Catharine Taylor; Jeffrey L. Jacobs (BMC, 2023)
Abstract Introduction Low- and middle-income countries (LMICs) are committed to achieving the Sustainable Development Goal 3.1 to reduce maternal mortality. The Ministry of Health and Family Welfare of India recommends prophylactic uterotonic administration to every woman following delivery to reduce the risk of postpartum hemorrhage (PPH), as PPH is the leading cause of maternal mortality in LMICs, including India. In 2018, the World Health Organization first recognized heat-stable carbetocin for PPH prevention. Governments are now considering its introduction into their public health systems. Methods A decision-tree model was developed from the public healthcare system perspective to compare the value of heat-stable carbetocin versus oxytocin and misoprostol among women giving birth in public sector healthcare facilities in India. The model accounted for differences in PPH risk and costs based on mode of delivery and healthcare setting, as well as provider behavior to mitigate quality concerns of oxytocin. Model outcomes for each prophylactic uterotonic included the number of PPH events, DALYs due to PPH, deaths due to PPH, and direct medical care costs. The budget impact was estimated based on projected uterotonic uptake between 2022-2026. Results Compared to oxytocin, heat-stable carbetocin avoided 5,468 additional PPH events, 5 deaths, and 244 DALYs per 100,000 births. Projected direct medical costs to the public healthcare system were lowered by US $171,700 (₹12.8 million; exchange rate of ₹74.65 = US$1 from 2 Feb 2022) per 100,000 births. Benefits were even greater when compared to misoprostol (7,032 fewer PPH events, 10 fewer deaths, 470 fewer DALYs, and $230,248 saved per 100,000 births). In the budget impact analysis, India's public health system is projected to save US$11.4 million (₹849 million) over the next five years if the market share for heat-stable carbetocin grows to 19% of prophylactic uterotonics administered. Conclusions Heat-stable carbetocin is expected to reduce the number of PPH events and deaths, avoid more DALYs, and reduce costs to the public healthcare system of India. Greater adoption of heat-stable carbetocin for the prevention of PPH could advance India's efforts to achieve its maternal health goals and increase efficiency of its public health spending.